Perhitungan Titik Impas sebagai Dasar Perencanaan Laba - Riptiandi, Akmal Firli; Indrawati, Lili; Sudradjat, Sudradjat; Surya, Rendra Trisyanto (Jurusan Akuntansi Politeknik Negeri Bandung, 2025)
This research takes place at Kueqoe MSMEs which have not calculated the break event point, the purpose of this study is to calculate the number of Break-Even Points (BEP) at Kueqoe MSMEs. The research method used is quantitative. By classifying costs into fixed costs and variable costs, calculating contribution margins, BEP, sales volume targets. Based on the calculation, the resulting BEP is IDR 435,610.582. The results of this study are expected to help companies in planning optimal profits through BEP calculations.